Why do closed-end funds repurchase stock? - Tianna Yang (South African Journal of Business Management, 2018)
With special institutional characteristics and regulatory requirements, what factors can motivate UK closed-end funds to engage in open-market repurchases? Investigating repurchase transactions on financial-year basis, I find that funds repurchase shares to reduce discounts and to increase the net asset value per share, as directors claim, but not to increase fund liquidity. I also find that funds repurchase shares to increase leverage ratios. Unlike conventional firms, neither distributing excess cash nor substituting dividend payouts promote fund repurchases. Fund size has a negative effect on repurchase decision.
Keywords: 650